Real-time quantitative PCR to determine chlamydial load in men and women in a community setting. - Wiggins, R; Graf, S; Low, N; Horner, P (2009)
We used a PCR method to quantify the loads of Chlamydia trachomatis organisms in self-collected urine and vulvovaginal swab (VVS) samples from 93 women and 30 men participating in the Chlamydia Screening Studies Project, a community-based study of individuals not seeking health care. For women, self-collected VVS had a higher mean chlamydial load (10,405 organisms/ml; 95% confidence interval [95% CI], 5,167 to 21,163 organisms/ml) than did first-void urines (FVU) (503 organisms/ml; 95% CI, 250 to 1,022 organisms/ml; P < 0.001). Chlamydial loads in female and male self-collected FVU specimens were similar (P = 0.634). The mean chlamydial load in FVU specimens decreased with increasing age in females and males. There was no strong statistical evidence of differences in chlamydial load in repeat male and female FVU specimens taken when patients attended for treatment a median of 23.5 (range, 14 to 62) and 28 (range, 13 to 132) days later, respectively, or in VVS taken a median of 35 (range, 14 to 217) days later. In this study, chlamydial load values for infected persons in the community who were not seeking treatment were lower than those published in other studies involving symptomatic patients attending clinical settings. This might have implications for estimates of the infectiousness of chlamydia. The results of this study provide a scientific rationale for preferring VVS to FVU specimens from women.